Safety and immunogenicity of a novel oral hexavalent rotavirus vaccine：a phase I clinical trial. Issue 7 (3rd July 2021) - Wu, Zhi-Wei; Li, Qing-Liang; Zhou, Hai-Song; Duan, Kai; Gao, Zhao; Zhang, Xin-Jiang; Jiang, Zhi-Jun; Hao, Zhi-Yong; Jin, Fei; Bai, Xuan; Li, Qi; Xu, Ge-Lin; et al.
ABSTRACT: Background Rotavirus infections, prevalent in human populations, are caused mostly by group A viruses. Immunization against rotaviruses in infancy is currently the most effective and economical strategy to prevent rotavirus infection. This study evaluated the safety of a novel hexavalent rotavirus vaccine and analyzed its dose and immunogenicity. Methods This randomized, double-blinded, placebo-controlled phase I clinical trial enrolled healthy adults, toddlers, and infants in Zhengding County, Hebei Province, northern China. 40 adults and 40 children were assigned in a 2:1:1 ratio to receive one vaccine dose, placebo 1, and placebo 2, respectively. 120 6–12 week old infants were assigned equivalently into 3 groups. The infants in each group were assigned in a 2:1:1 ratio to receive three doses of vaccine, placebo 1, and placebo 2, at a 28-day interval. Adverse events (AEs) until 28 days after each dose and serious adverse events (SAEs) until 6 months after the third dose were reported. Virus shedding until 14 days after each dose in infants was tested. Geometric mean concentrations (GMCs) and seroconversion rates were measured for anti-rotavirus IgA by using an enzyme-linked immunosorbent assay (ELISA). Results The solicited and unsolicited AE frequencies and laboratory indexes were similar among the treatment groups. No vaccine-related SAEs were reported. The average percentage of rotavirus vaccine shedding in the infant vaccine groups was 5.00%. The post-3rd dose anti-rotavirus IgA antibody geometric mean concentrations (GMC) and seroconversion rate were higher in the vaccine groups than in the placebo groups. Conclusions The novel oral hexavalent rotavirus vaccine was generally well-tolerated in all adults, toddlers and infants, and the vaccine was immunogenic in infants.